2016
DOI: 10.1002/oby.21414
|View full text |Cite
|
Sign up to set email alerts
|

Higher augmentation index is associated with tension‐type headache and migraine in middle‐aged/older humans with obesity

Abstract: Objective Obesity is a major risk factor for chronic daily headaches, including migraine and tension-type headache (TTH). Although migraine is associated with increased risk of cardiovascular diseases (CVD), a relation between TTH and CVD risk has not been established. It was hypothesized that higher carotid-femoral pulse wave velocity (CFPWV) and augmentation index (AI), measures of aortic stiffness and pressure wave reflection, respectively, and biomarkers of CVD risk, would be higher among adults with obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…This analysis uses baseline data from a clinical trial of pharmacotherapy for weight loss (http://ClinicalTrials.gov identifier NCT01351753) . Persons age 40 to 75 with a BMI ≥30 kg/m 2 and at least one additional risk factor for CVD (e.g., diabetes mellitus, elevated fasting glucose, hyperlipidemia, hypertension, metabolic syndrome) were eligible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis uses baseline data from a clinical trial of pharmacotherapy for weight loss (http://ClinicalTrials.gov identifier NCT01351753) . Persons age 40 to 75 with a BMI ≥30 kg/m 2 and at least one additional risk factor for CVD (e.g., diabetes mellitus, elevated fasting glucose, hyperlipidemia, hypertension, metabolic syndrome) were eligible.…”
Section: Methodsmentioning
confidence: 99%
“…Persons age 40 to 75 with a BMI ≥30 kg/m 2 and at least one additional risk factor for CVD (e.g., diabetes mellitus, elevated fasting glucose, hyperlipidemia, hypertension, metabolic syndrome) were eligible. Exclusion criteria have been described in detail elsewhere . Participants provided written informed consent as part of a University of Iowa Institutional Review Board‐approved protocol.…”
Section: Methodsmentioning
confidence: 99%
“…For example, higher AIx has been associated with increased cardiovascular risk (18,19), lower cardiorespiratory fitness (20), and increased clinical severity of coronary artery disease and percutaneous coronary intervention treatment in patients with a high Framingham risk score (18). In addition, higher AIx has also been associated with normotensive kidney disease (21), headaches and migraines in obese participants (22), and lower academic and motor performance in adolescents (23).…”
Section: Introductionmentioning
confidence: 99%
“…Carotid-femoral pulse wave velocity (CFPWV) is the gold standard non-invasive test to measure aortic stiffness 27 . In one study, 93 middle-aged/elderly obese adult subjects with at least one additional cardiovascular risk factor were grouped according to no headache, tension-type headache (TTH) or migraine and AI and carotid-femoral pulse wave velocity were measured as an indicator of aortic stiffness 28 . It was found that elevated AI was independently associated with the presence of either migraine or TTH, but could not discriminate between migraine and TTH.…”
Section: Discussionmentioning
confidence: 99%